2000
DOI: 10.1017/s0952523800171056
|View full text |Cite
|
Sign up to set email alerts
|

Burst and tonic firing in thalamic cells of unanesthetized, behaving monkeys

Abstract: Thalamic relay cells fire in two distinct modes, burst or tonic, and the operative mode is dictated by the inactivation state of low-threshold, voltage-gated, transient (or T-type) Ca 2ϩ channels. Tonic firing is seen when the T channels are inactivated via membrane depolarization, and burst firing is seen when the T channels are activated from a hyperpolarized state. These response modes have very different effects on the relay of information to the cortex. It had been thought that only tonic firing is seen i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
150
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 180 publications
(166 citation statements)
references
References 37 publications
15
150
0
1
Order By: Relevance
“…However, the coexistence of burst and tonic sensory responses reported here is in line with other studies in anesthetized and awake animals which demonstrate that sensory information is encoded through both tonic and burst spikes (10,37). Furthermore, bursts have been shown to be part of the sensory response during active tasks (8,11,16), and bursts are systematically related to the sensory input (Fig. 2); this relationship would not be expected if sensory relay is suppressed by bursts (38).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, the coexistence of burst and tonic sensory responses reported here is in line with other studies in anesthetized and awake animals which demonstrate that sensory information is encoded through both tonic and burst spikes (10,37). Furthermore, bursts have been shown to be part of the sensory response during active tasks (8,11,16), and bursts are systematically related to the sensory input (Fig. 2); this relationship would not be expected if sensory relay is suppressed by bursts (38).…”
Section: Discussionsupporting
confidence: 92%
“…In burst mode, sensory inputs are relayed as short, rapid clusters of APs; in contrast, in tonic mode the same inputs are translated into single APs. Both tonic and burst modes have been described during anesthesia/sleep and wakefulness/behavior, with a pronounced shift toward the tonic mode during alertness (8)(9)(10)(11)(12).…”
mentioning
confidence: 99%
“…11 and 38; for review see ref., 39) and in vivo (1,40). These results corroborate other studies that have shown bursting activity during wakefulness in cats (13,14), guinea pigs (15), rabbits (16), and monkeys (17,18). Thus, it is clear that bursting can occur during wakefulness and, indeed, can be observed during periods of sensory processing (12)(13)(14).…”
Section: The Burst Firing Mode Is Not Limited To Sleep and Pathologicsupporting
confidence: 87%
“…11 for review), such as during slow-wave sleep, barbiturate anesthesia, and pathological conditions such as seizure activity. However, it has recently been demonstrated that thalamic bursting can occur during awake states as well, in multiple species (12)(13)(14)(15)(16)(17)(18), and that sensory information can be conveyed to the cortex during the burst activity (16).…”
mentioning
confidence: 99%
“…If visual TRN neurons project back to the LGN neurons from which they receive their inputs (to the neurons representing the same part of the visual field), they would form "closed loop" connections, resulting in feedback inhibition. It has been suggested that during wakefulness, feedback inhibition initiates a rhythmic burst firing in LGN relay neurons, which may serve to alert visual cortex of behaviorally relevant sensory input (Crick, 1984;Sherman and Guillery, 1996) and facilitate signal transmission during visual target acquisition and early phases of fixation (Guido and Weyand, 1995; also see Ramcharan et al, 2000). The predominant increase in visual TRN activity that we have shown would be consistent with this view, because this increase in activity would be passed to the LGN as an increase in inhibition, resulting in the hyperpolarization of the LGN membrane and the consequent switching of these visual thalamic relay neurons from tonic to burst mode (Llinas and Jahnsen, 1982;Jahnsen and Llinas, 1984a,b;Sherman and Koch, 1986).…”
Section: Trn Modulation With Attentionmentioning
confidence: 99%